RESERVES TO AVOID CURRENCY RISKS IN THE CONTEXT OF MARKET RELATIONS - Gafurov Olimjon Ghalib Ugly (Scholar Express Journals, 2024)
The article describes instruments for managing currency risks in the context of market relations. The latest statistics on the relevant indicators are provided. Conclusions and suggestions are given on how to protect Uzbekistan from currency risks.
Keywords: foreign currency reserves; hedging; swap; option